Studies on Seeds, Germination Success and Raised Seedlings of Nypa fruticans - Siddiqi, N. A.; Shahidullah, M.; Shahjalal, M. A. H. (Indian Forester, 1991)
Studies on fruiting time, germination success, seedling raising, seedling growth and survival after out planting were carried out from 1987 to 1989 in the Sundarbans mangrove forest. Matured seeds were mainly available from February to April. Weight of a seed varied from 80 to 120 gm and on average 1 kg contained 10 to 12 seeds. Germination of seeds was 92 to 95% and yearly variation in germination was not noticed. Within 60 days the seedlings attained an average height of 24 cm. Maximum survival (68%) was obtained from planting larger seedlings.